Experimental and Clinical Use of Therapeutic Hypothermia for Ischemic Stroke: Opportunities and Limitations - Tine Zgavc; An-Gaëlle Ceulemans; Sophie Sarre; Yvette Michotte; Said Hachimi-Idrissi (Stroke Research and Treatment)
Stroke remains a disease with a serious impact on quality of life but few effective treatments exist. There is an urgent need to develop and/or improve neuroprotective strategies to combat this. Many drugs proven to be neuroprotective in experimental models fail to improve patient outcome in a clinical setting. An emerging treatment, therapeutic hypothermia (TH), is a promising neuroprotective therapy in stroke management. Several studies with TH in experimental models and small clinical trials have shown beneficial effects. Despite this, implementation into the clinical setting is still lacking due to methodological considerations as well as hypothermia-related complications. This paper discusses the possible opportunities and limitations of the use of TH in animal models and the translation into the clinic.